Transcatheter closure of tubular type patent ductus arteriosus using AmplatzerÂ® ductal occluder II: a case report - Mulyadi M Djer; Nikmah Salamia Idris; Angelina Angelina (Indonesian Pediatric Society, 2013)
Patent ductus arteriosus (PDA) is a common congenital heart disease, accounting for 5-10% of all congenital heart diseases. The incidence of PDA is even higher in preterm neonates, ranging from 20-60%.1-4 Closure of PDA is indicated in all cases, except for duct-dependent congenital heart diseases or PDA with Eisenmenger syndrome.1,5,6 In small asymptomatic PDAs, closure is indicated to prevent the risk of complications, such as endarteritis, endocarditis, aneurysm of ductus arteriosus, or congestive heart failure.1,2,7In recent years, interventional cardiology has become a gold standard therapy for the majority of PDA cases beyond neonatal age. Since its introduction in 1967, many devices and methods have been developed to allow transcatheter closure of virtually all PDAs, regardless of size or configuration. Nevertheless, the tubular shape (type C) PDA, which has the highest residual shunt rate, still poses a great challenge for the interventionist.8-10 The second generation of AmplatzerÂ® device occluders (ADO II), released in 2007, has been suggested to be effective in closing tubular PDAs.10 The purpose of this study was to report the initial clinical experience using ADO II to close a tubular type PDA in Indonesia.